2009
DOI: 10.2214/ajr.08.1858
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Classifier for Predicting Malignant Renal Cysts on MDCT: Early Clinical Experience

Abstract: ). G e n it o u r i n a r y I m ag i ng • O r ig i n a l R e s e a rc hWEB This is a Web exclusive article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There are two general approaches to creating BN models: first, inputting data for the BN to "learn" and, second, building them based on data in the literature, expert knowledge, or both. In the first approach, the parameters of the BN are learned by mining a large dataset of cases in which the diagnoses of the cases are established [9]. This approach requires a large dataset for training and could be impractical because it requires thousands of annotated cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two general approaches to creating BN models: first, inputting data for the BN to "learn" and, second, building them based on data in the literature, expert knowledge, or both. In the first approach, the parameters of the BN are learned by mining a large dataset of cases in which the diagnoses of the cases are established [9]. This approach requires a large dataset for training and could be impractical because it requires thousands of annotated cases.…”
Section: Discussionmentioning
confidence: 99%
“…These models have been used in many areas of medicine to estimate the probability of disease, such as diagnosing renal cystic lesions, predicting breast cancer risk, and identifying deep venous thrombosis [6][7][8][9].…”
mentioning
confidence: 99%
“…In fact, from the articles analyzed, it emerges that, according to the CT acquisition phase taken into consideration, the results obtained change; specifically, the most used phase is the corticomedullary phase [30]. Furthermore, as regards the use of CT for the extraction of characteristic features, the literature considers the three-dimensional use of CT to be better and more representative [117], but in the research identified [27][28][29][30][31][32][33][34][35][36], to reduce the workload of manual segmentation and facilitate the repeatability of this operation, a limited number of slices or only the two-dimensional slice containing the largest portion of the mass considered is used. In addition to how CT is used, it is also important to control the method by which features are extracted; in some research [28,29,[31][32][33][34][35][36], radiomic features are used, after manual segmentation by at least one experienced physician, to classify tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To face this challenge, modern ML techniques have been employed to process image data, proving to help physicians in making a more precise and accurate diagnosis. To classify and distinguish between malignant and benign masses, [27] some use a Bayesian classifier [28], a learning algorithm based on the statistical relationship between radiomics features (relational functional gradient boosting), and [29] an algorithm based on CT texture analysis. Many works focus on the analysis of renal cell carcinoma (RCC), which is the cause of 80% of kidney cancer deaths [25], either to distinguish different types of RCCs or to differentiate them from benign tumors.…”
Section: Kidney Massesmentioning
confidence: 99%
“…Many earlier studies have shown that machine learning approaches can be used to stratify CRL ( 23 , 24 ). However, only a few studies rely on pathology as the diagnostic criteria ( 25 ).…”
Section: Discussionmentioning
confidence: 99%